Pendidikan Pola Komunikasi Siswa dengan Guru dalam Menciptakan Suasana Belajar Akademik yang Kondusif - Rima Emilia; Anisa Qutrun Nada; Serlina Anggi Vionetta; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Communication is a very important activity in life, including in the context of education. This study aims to explore the level of communication between students and teachers and its impact on the learning atmosphere. In education, effective communication between teachers and students plays a key role in forming a smooth and conducive learning process. This study shows that a two-way relationship between teachers and students can improve students' understanding of the material and learning motivation. The results of the study convey that communication barriers, such as language disparities and an unsupported learning environment, can interfere with the learning process. Therefore, it is crucial to identify these barriers in order to apply effective tactics to overcome them and improve the quality of learning. A friendly, concise, and attentive teacher communication style has been shown to create a more enjoyable and productive learning experience. This study also emphasizes the importance of shared communication that can influence students' emotions and empathy, as a result of creating a conducive and effective learning atmosphere. Overall, this study is needed to contribute theory and practice to understanding the dynamics of communication in education, and as a basis for teachers to improve the quality of communication in the learning process.